Firm-level disclosure in the Baltic and Nordic regions before and after the mandatory adoption of the IFRS - Yuan Ding; Hannu Schadewitz (Richards College of Business, the State University of West Georgia, 2025)
This study systematically examines the levels of disclosure (i.e. the availability of firm-specific information to those outside publicly traded firms, measured by disclosure indices) in the annual reports of firms from the Baltic states of Estonia, Latvia and Lithuania, and compares the results with a sample of Nordic firms. The Baltic and Nordic regions are members of the EU and have had the same accounting regulations and stock market structure since 2005. In order to focus on and isolate the effect of regulation change on disclosure as reliably as possible, the time period used in this paper is 2004 and 2006, i.e. one year before and one year after the mandatory adoption of the IFRS. NASDAQ OMX owns and operates (with similar trading and quotation mechanisms) the stock exchanges that list all of our sample firms. The countries in our sample also have similar corporate governance regulations and recommendations for their listed firms. These similarities enable us to analyze whether other institutional and economic related factors, i.e. remaining matters that rule, regulate and monitor firms’ legal duties and the role of stock markets in an economy, and the principal societal differences in the sample countries, influence firms’ disclosure practices. We find that the level of financial reporting disclosure in annual reports is lower for Baltic firms than for Nordic firms, both before and after the introduction of the EU mandated International Financial Reporting Standards (IFRS) in 2005. However, the regulated financial reporting disclosure of Estonian firms matches that of their Nordic counterparts. This outcome is in line with the early proactivity and long-range strategy of regulators in Estonia aligning Estonia’s GAAP with the IAS/IFRS. Our results support the conclusion that disclosure practices are affected by factors beyond the IFRS and the similarity between the regions’ market trading and quotation mechanisms. This study provides evidence that systematic and strong-enough regulatory actions influence disclosure practices. We also hope that the disclosure indices described in this paper will help managers recognize the potential and richness of financial reporting disclosure as a communication tool.